The Role of the Notary in Making and Registering a Testament Deed - Purwaningtyas, Ditha Aprilia (Jurnal Konstatering, 2022)
Notary as a Public Official who has the authority to make authentic deeds as stated in Article 15 paragraph (1) of Act No. 2 of 2014 concerning the Office of a Notary, one of which is making a will. This study aims to identify and analyze the role of a notary in making and registering a will and testament at BHP Kota Semarang and the responsibilities of a notary who does not register the deed of testament he has made. The research method used is the sociological juridical research method. The research specification uses a descriptive type of analysis using primary data sources and secondary data. Methods of data collection through field studies and literature studies. The analytical knife in answering the problem uses the theory of authority and the theory of legal certainty. The results of the study show that the role of the Notary in making wills according to the Civil Code is in the form of: making Supercriptie Deeds relating to explanations regarding secret wills and signing the deed and keeping them, keeping wills, keeping wills, making deed of appointment of executors of wills, and making deed Appointment of the manager of the inheritor's assets. According to the Compilation of Islamic Law (KHI), the role of a notary in making wills is in the form of making wills and deed of revocation of wills. Then, the Notary also plays a role in registering the will at the Heritage Agency (BHP). Ensure that the will has been registered and registered with BHP. The responsibility of the notary if he fails to register the will is a substantive responsibility.Keywords: Deed;Heritage; Treasure.